Faktor-Faktor yang Berhubungan dengan Perilaku Ibu Terhadap Pemeriksaan Mata di Anak-Anak di Puskesmas Gunungpati Semarang - Dedeh Kurniasih; Trilaksana Nugroho; Andhika Guna Dharma (JURNAL IMPLEMENTA HUSADA, 2020)
Introduction: Early years of life are very important in the development of eyes and vision. Each disorder at this stage can cause severe visual impairment or blindness. Eye examination in children is not only the child's right, but also the obligation of the parents to monitor and evaluate it.Objectives: To determine the relationship of socio-demographic factors and knowledge with the behavior of mothers towards eye examinations in children in the Gunung Pati Primary Health Care, Semarang.Methods: This study was an observational analytic with a cross sectional approach. The sample size was 47 respondents. The instrument used was a questionnaire that had previously been tested for validity and reliability. Data were analyzed using SPSS 15.0 statistical test techniques with Chi square test.Results: There was a significantly correlation between the level of education with the behavior of mothers ( p=0.004), and between the knowledge with behavior of mothers towards eye examination in their children (p=0,018). The multivariate analysis showed that the knowledge was the most dominant factor determine the behavior of the mother (p=0.03; OR=5,74; 95% CI=1,12-29,46).Conclusion: Appropriate maternal education and counseling strategies on the basis of eye health examinations and the importance of undergoing regular eye examinations are needed in improving eye health in children.